SANG PELAUT DARI BELITUNG: DAMPAK TINGGAL DI DARAT TERHADAP KEHIDUPAN SOSIALBUDAYA SUKU SAWANG (1936-2012) - Eki Ripan J.P.R; Leli Yulifar (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This study aimed to describe the dynamics life of Sawang People as a Sea Nomads in Belitung Island. In 1936, since Sawang People start to be employed in Dutch minning, until the relocation policy by Indonesian government that carried out the relocation from the sea to the land from 1970 to 2012, already have some positive and negative impact against the sustainability of maritime culture of Sawang People as they began settled on land. The Positive impact is force Sawang People to adapt with the age of development and mingle with the Belitung community on land. The Negative impact caused some positive maritime culture of Sawang became nearly extinct like the language of Sawang, art, traditional knowledge, and maritime values in line with decreasing of native Sawang People on Belitung Island.